Balancing work and life during the COVID-19 pandemic: mental health intervention in FEB UGM - Margarini, Dita (Berita Kedokteran Masyarakat, 2021)
Objective: The purpose of this research was to improve knowledge and behavior about mental health for staff and students in the Faculty of Economics and Business Universitas Gadjah Mada (FEB UGM) during the COVID-19 pandemic through a webinar. The webinar’s topic was work-life balance, how to managing stress to balance work and life. A preliminary survey for students and staff found mental health is the biggest of health problems in FEB UGM. This research was the program for implementing Health Promoting University. Method: A mixed methods research design, comprising one group pre-test post-test design and semi-structured interviews. The participants had answered the pre-test using google form before the webinar started and answered the post-test after the speaker had finished the presentation. The data were analyzed using SPSS version 26. Five participants who attended the webinar were interviewed. Results: A total of 153 webinar participants were staff and students in FEB UGM. The average scores for knowledge increased from 78.56 to 87.32. There was a significant difference in knowledge scores between pre-test and post-test (p < 0.05). The interview results show that the participants have changed their attitude and behavior to control their stress and balance their work and life. Conclusion: Webinar during COVID-19 pandemic effectively improved knowledge, attitude, and behavior about mental health, especially to balance work and life during the pandemic. Webinars or other educational strategies should be held periodically to maintain mental health for students and staff.